Interactions, Relationships, and Networks are Essential Foundations of Competitive Advantage: A Comprehensive Review - Onur GUVENC (Communications of International Proceedings, 2021)
This paper investigates interactions, relationships, and networks in a fluctuating business landscape. The paper reflects on the aspects of the context of transformation and the researcher used a qualitative approach based on its ability to generate hypothesis and knowledge on the subject. A set of questions guided this research. The approach was chosen based on the need to gain insight into the phenomenon of interactions, relationships, and networks and their role in a fluctuating business landscape. The use of a literature review as a research methodology was considered to be essential based on the increased theoretical and practical contribution it has to the study. The use of secondary research entailed a summary, synthesis, and collation of existing research. The paper found that companies operating in the modern age are subjected to change in their interactions, relationships, and networks based on the need to achieve sustainability production. They have achieved this through their embracement of new operating norms and technologies. The drive to make the changes is influenced by the need for sustainable development, digitization, and circular economy. The shift has also been fuelled by the existence of tools and technologies that pressure companies’ adaptability to remain competitive. The research also found that success and failure of a business are dependent on its ability to respond to the changing external setting. The research is valuable to business that seek to understand interactions, relationships and networks in a changing business landscape.
Keywords: Networks; Customer/Business Relationship Management; Information Technology; Changing Business Landscape; Globalisation.